THE COMPOSITION OF THE MICROBIOTES OF THE NECK PART OF THE TEETH IN THE AREA OF THE GUM EDGE OF RATS AT THE END OF THE SECOND, FOURTH AND SIXTH WEEKS OF OPIOID INFLUENCE (World Science, 2020)
The aim of the study was to investigate the microbiota in the cervical part of the teeth in the gingival margin of the oral cavity of rats at the end of the second, fourth and sixth weeks of the experimental action of the opioid analgesic nalbuphine. Under the action of opioids for six weeks, changes in the microbiocenosis in the studied subbiotope of the oral cavity of animals were found, which manifested themselves in the early stages by the appearance of gram-negative anaerobes, gradual increase in opportunistic pathogens, formation of dental biofilm experiment.